Analysis of Various Physico-Chemical Factors of Gang Canal Near Sri Ganganagar (Rajasthan): Assessment of Physico-Chemical Factors and Suitability of Gang Canal Water for Agriculture and Fish Production (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The present study describes the water quality of Gang Canal near Sri Ganganagar city. Theresult of this study efforts were made to evaluate the chemicalcharacteristics of Gang canal. The Watersamples were analyzed for pH, hardness, and dissolved O, which are essential parameters for humanand animalconsumption. The average value of Hardness is 150 mgl which indicates that itis slightly hardwater. The value of Do is 10.8 which represent good,concentration in water for respiration needed byliving organisms. The averagevalue of pH recorded in Gang canal is 8.5 which decides that water is basicinnature. So we concluded that Gang Canal water is suitable for agriculture and fish production.